The Influence of Nutrition in Alzheimer's Disease: Neuroinflammation and the Microbiome vs. Transmissible Prion - Bello-Corral, Laura; Sánchez-Valdeón, Leticia; Casado-Verdejo, Inés; Seco-Calvo, Jesús Ángel; Antonio Fernández-Fernández, Jesús; Nélida Fernández-Martínez, María (Frontiers in Neuroscience, 2021)
Alzheimer's disease (AD) is a primary, progressive, neurodegenerative disorder. Many risk factors for the development of AD have been investigated, including nutrition. Although it has been proven that nutrition plays a role in AD, the precise mechanisms through which nutrition exerts its influence remain undefined. The object of this study is to address this issue by elucidating some of the mechanisms through which nutrition interacts with AD. This work is a qualitative systematic bibliographic review of the current literature searchable on various available databases, including PubMed, Web of Science, and Google Scholar. Our evidence comprises 31 articles selected after a systematic search process. Patients suffering with AD present a characteristic microbiome that promotes changes in microglia generating a proinflammatory state. Many similarities exist between AD and prion diseases, both in terms of symptoms and in the molecular mechanisms of pathogenesis. Changes in the composition of the gut microbiome due to dietary habits could be one of the environmental factors affecting the development of AD; however, this is probably not the only factor. Similarly, the mechanism for self-propagation of beta-amyloid seen in AD is similar to that seen in prions.